Assessing in vivo and in vitro biofilm development by Streptococcus dysgalactiae subsp. dysgalactiae using a murine model of catheter-associated biofilm and human keratinocyte cell - Alves-Barroco, Cinthia; Botelho, Ana Maria Nunes; Américo, Marco Antonio; Fracalanzza, Sérgio Eduardo Longo; de Matos, António P. Alves; Guimaraes, Márcia Aparecida; Ferreira-Carvalho, Bernadete Teixeira; Figueiredo, Agnes Marie Sá; Fernandes, Alexandra R. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus dysgalactiae subsp. dysgalactiae (SDSD) is an important agent of bovine mastitis. This infection causes an inflammatory reaction in udder tissue, being the most important disease-causing significant impact on the dairy industry. Therefore, it leads to an increase in dairy farming to meet commercial demands. As a result, there is a major impact on both the dairy industry and the environment including global warming. Recurrent mastitis is often attributed to the development of bacterial biofilms, which promote survival of sessile cells in hostile environments, and resistance to the immune system defense and antimicrobial therapy. Recently, we described the in vitro biofilm development on abiotic surfaces by bovine SDSD. In that work we integrated microbiology, imaging, and computational methods to evaluate the biofilm production capability of SDSD isolates on abiotic surfaces. Additionally, we reported that bovine SDSD can adhere and internalize human cells, including human epidermal keratinocyte (HEK) cells. We showed that the adherence and internalization rates of bovine SDSD isolates in HEK cells are higher than those of a SDSD DB49998-05 isolated from humans. In vivo, bovine SDSD can cause invasive infections leading to zebrafish morbidity and mortality. In the present work, we investigated for the first time the capability of bovine SDSD to develop biofilm in vivo using a murine animal model and ex-vivo on human HEK cells. Bovine SDSD isolates were selected based on their ability to form weak, moderate, or strong biofilms on glass surfaces. Our results showed that SDSD isolates displayed an increased ability to form biofilms on the surface of catheters implanted in mice when compared to in vitro biofilm formation on abiotic surface. A greater ability to form biofilm in vitro after animal passage was observed for the VSD45 isolate, but not for the other isolates tested. Besides that, in vitro scanning electron microscopy demonstrated that SDSD biofilm development was visible after 4 hours of SDSD adhesion to HEK cells. Cell viability tests showed an important reduction in the number of HEK cells after the formation of SDSD biofilms. In this study, the expression of genes encoding BrpA-like (biofilm regulatory protein), FbpA (fibronectin-binding protein A), HtrA (serine protease), and SagA (streptolysin S precursor) was higher for biofilm grown in vivo than in vitro, suggesting a potential role for these virulence determinants in the biofilm-development, host colonization, and SDSD infections. Taken together, these results demonstrate that SDSD can develop biofilms in vivo and on the surface of HEK cells causing important cellular damages. As SDSD infections are considered zoonotic diseases, our data contribute to a better understanding of the role of biofilm accumulation during SDSD colonization and pathogenesis not only in bovine mastitis, but they also shed some lights on the mechanisms of prosthesis-associated infection and cellulitis caused by SDSD in humans, as well.